Փորձառական տվյալներ հայերեն խոսքում դադարների դրսևորման վերաբերյալ - Գրիգորյան, Գայանե (ՀՀ ԳԱԱ ԼԻ հրատարակչություն)
A pause is a fully integrated part of intonation. The importance of pauses in spoken speech is great. The article examines the types, functions, duration, psychological significance, and importance of pauses in oral speech. For the first time, pauses in spoken speech were studied using an experimental method, examples and their sound images were given. In particular, the durations of pauses were calculated by types, pauses were classified according to different criteria. Special attention was paid to the pauses in public manifestation speech, since they are very popular in the nowadays socio-political sphere. Пауза- это полноценная часть интонации. Значение пауз в устной речи велико. В статье рассматриваются виды, функции, длительность, психологическое значение, важность пауз в устной речи. Впервые экспериментальным методօм изучены паузы звучащей речи, приведены примеры и их звуковые изображения. В частности, длительности пауз рассчитывались по типам, паузы классифицировались по разным критериям. Особое внимание было уделено проявлению пауз в публичной речи, поскольку они очень популярны в современной общественно-политической сфере.
Keywords: Լեզվաբանություն